Effects of periodic wakes on boundary layer development on an ultra-high-lift low pressure turbine airfoil. (February 2017) - Lu, Xingen; Zhang, Yanfeng; Li, Wei; Hu, Shuzhen; Zhu, Junqiang
The laminar-turbulent transition process in the boundary layer is of significant practical interest because the behavior of this boundary layer largely determines the overall efficiency of a low pressure turbine. This article presents complementary experimental and computational studies of the boundary layer development on an ultra-high-lift low pressure turbine airfoil under periodically unsteady incoming flow conditions. Particular emphasis is placed on the influence of the periodic wake on the laminar-turbulent transition process on the blade suction surface. The measurements were distinctive in that a closely spaced array of hot-film sensors allowed a very detailed examination of the suction surface boundary layer behavior. Measurements were made in a low-speed linear cascade facility at a freestream turbulence intensity level of 1.5%, a reduced frequency of 1.28, a flow coefficient of 0.70, and Reynolds numbers of 50, 000 and 100, 000, based on the cascade inlet velocity and the airfoil axial chord length. Experimental data were supplemented with numerical predictions from a commercially available Computational Fluid Dynamics code. The wake had a significant influence on the boundary layer of the ultra-high-lift low pressure turbine blade. Both the wake's high turbulence and the negative jet behavior of the wake dominated the interaction between the unsteady wake and the separated boundary layer on the suction surface of the ultra-high-lift low pressure turbine airfoil. The upstream unsteady wake segments convecting through the blade passage behaved as a negative jet, with the highest turbulence occurring above the suction surface around the wake center. Transition of the unsteady boundary layer on the blade suction surface was initiated by the wake turbulence. The incoming wakes promoted transition onset upstream, which led to a periodic suppression of the separation bubble. The loss reduction was a compromise between the positive effect of the separation reduction and the negative effect of the larger turbulent-wetted area after reattachment due to the earlier boundary layer transition caused by the unsteady wakes. It appeared that the successful application of ultra-high-lift low pressure turbine blades required additional loss reduction mechanisms other than "simple" wake-blade interaction.